Maternal outcome of prenatally diagnosed lethal fetal anomalies: a year review - Abdulwahab, Dalia F; Leong, Yoon Soon; Ismail, Hamizah; Awang, Mokhtar; Nusee, Zalina; Ismail, Rozihan (2012)
This was a retrospective review in Hospital Tengku Ampuan Afzan, Kuantan, Malaysia In the year of 2011. All patients diagnosed prenatally to carry lethal fetal anomalies was Reviewed. The outcome of the pregnancy including type of labour, mode of induction and delivery, and associated morbidities during antenatal, intrapartum, and postpartum period was analysed